CNVs-microRNAs Interactions Demonstrate Unique Characteristics in the Human Genome. An Interspecies in silico Analysis - Dweep, Harsh (Public Library of Science, 2013)
MicroRNAs (miRNAs) and copy number variations (CNVs) represent two classes of newly discovered genomic elements that were shown to contribute to genome plasticity and evolution. Recent studies demonstrated that miRNAs and CNVs must have co-evolved and interacted in an attempt to maintain the balance of the dosage sensitive genes and at the same time increase the diversity of dosage non-sensitive genes, contributing to species evolution. It has been previously demonstrated that both the number of miRNAs that target genes found in CNV regions as well as the number of miRNA binding sites are significantly higher than those of genes found in non-CNV regions. These findings raise the possibility that miRNAs may have been created under evolutionary pressure, as a mechanism for increasing the tolerance to genome plasticity. In the current study, we aimed in exploring the differences of miRNAs-CNV functional interactions between human and seven others species. By performing in silico whole genome analysis in eight different species (human, chimpanzee, macaque, mouse, rat, chicken, dog and cow), we demonstrate that miRNAs targeting genes located within CNV regions in humans have special functional characteristics that provide an insight into the differences between humans and other species.